2002
DOI: 10.1002/gene.10095
|View full text |Cite
|
Sign up to set email alerts
|

Axes establishment during eye morphogenesis in Xenopus by coordinate and antagonistic actions of BMP4, Shh, and RA

Abstract: We have examined the roles of BMP4, Shh, and retinoic acid in establishing the proximal-distal and dorsal-ventral axes in the developing Xenopus eye. Misexpression of BMP4 caused the absence of an optic stalk and the expansion of dorsal and distal markers, tbx2/3/5, and pax6, at the expense of ventral and proximal markers vax2 and pax2. When Shh or Noggin, an antagonist of BMPs, was misexpressed, the reverse expression patterns of these marker genes were observed. These results suggest that BMP4 is involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 58 publications
12
103
0
Order By: Relevance
“…Loss of Bmp signaling during blastula stages and early gastrulation leads to an expanison of proximo-ventral (PV) optic cell types (optic stalk), whereas dorso-distal (DD) cell types (neural retina and RPE) are reduced or lost, indicating a general ventralization of the optic primordia. Thus, dorso-ventral patterning of the optic primordia and specification of dorsal optic cell types is not only governed by Bmp4 generated in dorsal retina cells, as recently suggested from studies carried out in Xenopus (Sasagawa et al, 2002) and chick (Koshiba-Takeuchi et al, 2000; Sakuta et al, 2001), rather, this later Bmp function appears to reinforce a pattern already set up by Bmp signaling during gastrulation. Such early Bmp signals are generated in ventrolateral cells of all germ layers of the gastrulating embryos, promoting future ventral fates in endoderm and mesoderm, and dorsal fates in the neuroectoderm (Barth et al, 1999;Nguyen et al, 2000), including-as shown herethe eye primordia.…”
Section: Phenotypic Traits Of Mm169mentioning
confidence: 71%
See 2 more Smart Citations
“…Loss of Bmp signaling during blastula stages and early gastrulation leads to an expanison of proximo-ventral (PV) optic cell types (optic stalk), whereas dorso-distal (DD) cell types (neural retina and RPE) are reduced or lost, indicating a general ventralization of the optic primordia. Thus, dorso-ventral patterning of the optic primordia and specification of dorsal optic cell types is not only governed by Bmp4 generated in dorsal retina cells, as recently suggested from studies carried out in Xenopus (Sasagawa et al, 2002) and chick (Koshiba-Takeuchi et al, 2000; Sakuta et al, 2001), rather, this later Bmp function appears to reinforce a pattern already set up by Bmp signaling during gastrulation. Such early Bmp signals are generated in ventrolateral cells of all germ layers of the gastrulating embryos, promoting future ventral fates in endoderm and mesoderm, and dorsal fates in the neuroectoderm (Barth et al, 1999;Nguyen et al, 2000), including-as shown herethe eye primordia.…”
Section: Phenotypic Traits Of Mm169mentioning
confidence: 71%
“…This ventral movement of RPE precursor cells is thought to be one of the driving forces of eye morphogenesis (Li et al, 2000). The neural retina itself also displays a distinct dorso-ventral pattern, reflected by differential patterns of gene expression (Sasagawa et al, 2002, and references therein) and differential retinotectal projections (Chien and Harris, 1994;Baier et al, 1996). Different signaling processes have been implicated in PV-DD patterning of the eye primordia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, SHH induces supernumerary whisker buds in mice (Ohsaki et al, 2002) while either increased SHH signaling or blockade of BMP signaling during development of chick feather tracts (pterylae) both result in the formation of supplementary pterylae (Fliniaux et al, 2004). Furthermore, the balance of BMP and SHH signaling has also been shown to be important for regulation of somite growth and development (Amthor et al, 1999), interneuron development from telencephalic progenitors (Gulacsi and Lillien, 2003), and establishment of dorsoventral boundaries in the developing eye (Sasagawa et al, 2002). Results both identifying SHH and BMP4 as potential regulators of budding and showing that perturbations of SHH and BMP4 signaling produce supernumerary buds support the hypothesis that RA-induced changes in their ratio may stimulate prostatic bud formation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies on apparently homoplastic structures, such as the pharyngeal teeth in teleosts, have been emphasizing the neo-deployment of developmental cascades and the potential heterochronic, heterotopic, and heterofacient changes that may be accompanying (e.g., Fraser et al, 2004). Moreover, were examined, the importance of Fgf, endothelin, RA, Bmp, and Shh for cephalogenesis has also been established in amphibians and zebrafish (e.g., Ellies et al, 1997;Reifers et al, 1998;Degitz et al, 2000;Shanmugalingham et al, 2000;Miller et al, 2000;Koide et al, 2001;Sasagawa et al, 2002;Crump et al, 2004;Furthauer et al, 2004, Wilson andGroppelli et al, 2005;Albertso and Yelick, 2005;Reversade et al, 2005).…”
Section: Comparing the Components Of "Hinge And Caps" Model Between Taxamentioning
confidence: 99%